Contribution to the fresh water Tardigrada from Barentsøya, Svalbard (78°30'N) - E.A. Van Rompu; Willem H. De Smet (Fauna Norvegica)
Fifteen species and one subspecies of Tardigrada were found in the littoral zone of 18 fresh water bodies on the Talaveraflya. All taxa are new records for Barentsøya; Hypsibius antarcticus and Macrobiotus dianeae were not previously reported from Svalbard. A faunal survey (comprising 30 taxa) for all high arctic water bodies studied to date is given. The most frequently and numerously encountered fresh water species are Isohypsibius granulifer and Hypsibius dujardini, and to a lesser extent Isohypsibius papillifer, I. papillifer bulbosus and Macrobiotus dianeae.